2012
DOI: 10.1165/rcmb.2012-0079oc
|View full text |Cite
|
Sign up to set email alerts
|

Acute Inflammation Induces Insulin-like Growth Factor-1 to Mediate Bcl-2 and Muc5ac Expression in Airway Epithelial Cells

Abstract: Generally, exposure to LPS in human airways occurs in the form of aerosols and causes an acute inflammatory response or exacerbates existing chronic inflammatory conditions by enhancing airway remodeling and associated pathologies. The present study evaluated which inflammatory mediators may be responsible for the expression of Bcl-2 and mucus cell metaplasia when mice are exposed to aerosolized LPS. At 3 days after exposure, aerosolized LPS (for 20-40 min) with the estimated lung deposited dosage of 0, 0.02, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Various cell types expressing IGF-1 are found within the lung, including alveolar macrophages, bronchial epithelial cells, and fibroblasts, hence participation of IGF-I in lung disease pathogenesis has been widely reported (40,41). However, circulating IGF-I levels and pathogenic involvement are still unknown in the context of COPD (42).…”
Section: Discussionmentioning
confidence: 99%
“…Various cell types expressing IGF-1 are found within the lung, including alveolar macrophages, bronchial epithelial cells, and fibroblasts, hence participation of IGF-I in lung disease pathogenesis has been widely reported (40,41). However, circulating IGF-I levels and pathogenic involvement are still unknown in the context of COPD (42).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, adult mouse lungs displayed the highest level of Igf1r activation of any organ in the mouse upon challenge with Igf1 [52]. This local auto/paracrine action of Igf1/Igf1rcould be relevant not only in airway epithelial cellregeneration, but also foralveolar macrophagefunction, a cell type that also expresshigh levels of both proteins[53, 54]. Furthermore, Igf1r expression in smooth muscle and endothelial cells of pulmonary blood vessels also indicates a role of this receptor in lung vasculature, as described elsewhere [55, 56].…”
Section: Discussionmentioning
confidence: 99%
“…Both IL-1b and IL-18 are secreted as pro forms, and the activated forms are released by the proteolytic activity of caspase-1 as the component of a multiprotein complex referred to as inflammasome. B cell lymphoma (Bcl)-2 and Bcl-X L , primarily known as cell death regulators, are increased in AECs in response to CS or LPS (44)(45)(46), and modulate inflammatory responses by interacting with inflammasome and inhibiting processing of pro-IL-1b and pro-IL-18 (47). Structure-function studies have shown that a 50-aa flexible loop between the first and second a helices of Bcl-2 and Bcl-X L inhibit oligomerization of nucleotide-binding oligomerization domain-like receptor (NLR) pyrin domain containing 1, a prominent member of NLRs and a central component of inflammasome (48).…”
Section: Contribution Of Epithelial Cells To Cs-induced Inflammatory mentioning
confidence: 99%